Sharia Cooperative Institutional Development: The Block Chain Approach (Case Study in Bulak, Surabaya City) - Masroro Lilik Ekowanti; Aniek Sulestiani; Wildan Taufik Raharja (Universitas Muhammadiyah Sidoarjo, 2020)
A community-based institutional building of syariah cooperatives requires information and communication technology. This has led to a block chain approach that benefit from the industrial revolution 4.0. The institutional concept that was developed 60 years ago by JE. Eaton (1972) is very relevant in this context. In this study, we employ a qualitative method with descriptive research. Our findings shows that community response to knowledge and awareness for adopting syariah cooperative is satisfactorily good as indicated by the establishment of a syariah pra-cooperative named